Energy & mass balance in wet process coconut oil extraction - Bajacan, Allen Roy C. (Animo Repository, 1999)
To establish the energy and mass balances of the wet process of coconut oil extraction is the main concern of this study. Another concern of the study is to determine the amount of energy that can be utilized from the coconut shell as burning fuel to provide the heat energy required for the proposed wet process. In using the coconut shell to supply the energy required for the proposed wet process, the study aims to lessen the use of expensive sources of energy. The main difference of the proposed wet process to the conventional wet process is the steaming of the dehusked coconut before processing. Low temperature steam was used to easily separate the attachment of the coconut meat to the shell, making it more easy to be processed. After evaluating the energy and mass balances of the process, results showed that the energy content of the coconut shells was sufficient enough to supply the heat energy of the proposed wet process. The traditional and most popular method in extracting oil from the coconut is by the drying process. This process employ the copra as its raw material for extracting the oil. Some of the disadvantages and adverse effects of the copra drying process are also discussed in this study. Comparisons between the wet process and dry process were also considered. By making qualitative comparison between the two processes, the study aims to prove that wet process will be more advantageous and appropriate for the extraction of coconut oil.